Didyma, Türkei. Die Heilige Straße im Bereich des Apollontempels. Die Arbeiten der Jahre 2013 bis 2018 - Cevizoğlu, Hüseyin (e-Forschungsberichte des DAI, 2019)
The explorations of the sacred way between the city of Miletos and its extra-urban oracle sanctuary of Didyma have long played a central role in many research projects on the Milesian Peninsula. The interest in the Sacred Way goes back to the discovery made by William Gell in 1812 and it is still being researched at intervals. Although the route of the Sacred Way has also been explored by many systematic contemporary researches, thanks to surveys and excavations, some parts are still not reconstructed. The investigation of the uncertain section of the Sacred Way between the end of the Trajanic paved street and the area north of the Temple of Apollo at Didyma is the main subject of a new academic research Project conducted since 2013. Systematic excavations were carried out on the modern street in 2010 and between 2013 and 2015. In conjunction with the results of the current excavations around the temple we will thus be able to clarify the validity of conventional hypothesis about the existence of a way in the temple area.